Emerging Technologies and New Learning Ecologies: Learner’s Perceptions of Learning in Open and Networked Environments - Saadatmand, Mohsen; Kumpulainen, Kristiina (Proceedings of the International Conference on Networked Learning, 2012)
The emergence of networking technologies and social media is changing the way we work, collaborate and learn. This has resulted in new forms of learning practices, more participatory ways of creating and representing knowledge and new global learning networks. In the current era, learning and educational practices are becoming more open, digital and networked. Open and networked technologies provide the opportunities for online learning to offer kind of more open and flexible online learning opportunities which can bring together such a greater number of geographically-dispersed learners to experience kind of networked and collective learning mediated by online and web applications. Such open and free learning opportunities for instance are the growing interest in offering open online courses in higher education nowadays which attract many people. This paper discusses the learning activities and experiences of the participants of some open online courses who are coming from different parts of the world to online networked environments and integrate various tools and digital application in the process of their learning and interactions. This paper presents the preliminary findings of a research in progress on leaning ecologies in web 2.0 and emerging technologies and personal learning environment (PLE). The main research question for this paper is: what is the nature of learning in open and networked learning environments and what learning activities and experiences result from participating in these environments? The findings are based on an online survey, semi-structured interviews and public online contents of the participants in open online courses. This study adapted a virtual auto-ethnographic method to get involved more closely to the culture and phenomena of learning in such open online environments in which researcher was able as a learner to participate in the various activities of the courses, interact with participants to explore the processes of learning and interaction. For the purpose of data analysis and understanding the nature of learning and interactions in such open and networked environments, by reflection on socio-cultural theoretical frameworks such as social constructivism, communities of practice and connectivism, we used a rhizomatic approach to learning in networks and communities (Cormier, 2008, Engestrom, 2007, Tella, 2000) to look at different emergent and multi-directional learning activities take place in the context of such open environments and to explain how open-digital-networked technologies are used by participants of open online courses.